Magazine Design in Spanish Generalist Newspaper. Publico’s Covers - Mejia Chiang, César (2017)
This paper details thematic, as well as style and graphic language in Público newspaper's covers (October 2007 - June 2008). We assume that poster design in Público covers, during the cited period, exploited many visual resources (familiar with publications aimed to young readers and users of portable technologies and multimedia) and helped to canalize a systematic critic to “conservative” political sectors in Spain, underlining the “progressive” nature of this newspaper.